THE SUPERVISION ON THE IMPLEMENTATION OF JOB SAFETY ANALYSIS (JSA) AS THE EFFORT IN INCREASING BEHAVIOR BASED SAFETY (BBS) ON HIGH TENSE WORKING UNITS (HVWU) OF PT. PLN (PERSERO) MALANG AREA - Dewanto, Wisnu (PUSAT KEWIRAUSAHAAN UNIVERSITAS BALIKPAPAN, 2023)
JSA (Job Safety Analysis) is a method used to identify work that has potential hazards ao this method aims at making corrections before the accident happens. The purpose of Job Safety Analysis (JSA) is to explain the potential hazards that arise during the process of work on the working area and control the potential hazards. The supervision on the implementation of JSA is in accordance with the Company’s SOP (Standard opeating Procedure) which is expected to improve the Behavior Based Safety (BBS). Behavior Based Safety (BBS). is a corporate system to change unsafe behavior so that it can educate employees to look for causes of accident-prone behavior. This awakens employees behavior causing the risk of work accident. The observed behavior is documented and discussed in meetings, so that everyone can have a safer environment. The purpose of this study was to evaluate the implementation of Job Safety Analysis method. This research was located in PT. PLN Persero Malang Area. The subject of this research was focused on unit PDKB/High Tense Working Unit (HTWU) of PT. PLN (Persero) Malang Area. The sampling technique used in this research was purposive sampling and snowball sampling. The data collection techniques in this study used observation techniques, interviews, and documentation. The type of this research was descriptive qualitative case study. The results of this study indicate that High Tense Working Unit (HVWU) of PT. PLN (Persero) Malang Area has identified potential hazard periodically by using Job Safety Analysis method. Therefore, PT. PLN (Persero) Malang Area has a way of improving Behavior Based Safety (BBS) using JSA training, dismissal of workers, regulation socialization, implementation of safety awareness program and giving a sanction.